Sosialisasi Nilai Kesalehan Sosial dalam Fenomena Mudik bagi Masyarakat di Desa Maguwo Banguntapan Yogyakarta - Farida Musyrifah; Rizal Fathurrohman; Khanifuddin Khanifuddin (Universitas Alma Ata, 2024)
This research aims to analyze and describe the value of social piety in the homecoming phenomenon for the Maguwo Banguntapan Yogyakarta Community. With this type of field research and phenomenological approach, data collection was carried out through in-depth interviews and observations of several selected communities. Interviews and observations were conducted before and after returning home. The research results show that the homecoming phenomenon is based on the existence of a warm connection. The warm relationship between family members strengthens the spirit of meeting after one year of being overseas/outside the region for several reasons such as continuing studies, working and so on. The tradition of going home on Eid al-Fitr is characterized by several activities that are almost the same in all regions, such as: takbiran for Eid al-Fitr prayers, social gatherings and tours, grave visits, giving gifts and halal bihalal. The value of strengthening social piety from this homecoming phenomenon is in the form of increasing a person's religiosity, hard work, responsibility and social concern. In this way, the phenomenon of going home will always be of interest to the public, even though technology is already sophisticated (facilities of friendly communication) but it cannot yet replace the meaning of going home